Determinants of Islamic Bank Performance on Islamic Banking Profitability Ratios in Indonesia - Aninda Adistyana Dewi (International Journal of Islamic Studies Issues, 2025)
Purpose - This study aims to examine the performance of Islamic banks in Indonesia with a sample ratio of the vulnerable in 2016-2019 and provide benefits in academic activities. Integration in banking operators to pay attention to their financial management at risk and and in other ways to kaffah sharia business targets. Design/Methodology/Approach - Using a quantitative approach with the Vector Error Correction Model (VECM) data analysis technique due to the stationarity test at the 1st differn level and using time series sample data taken from June 2016 to June 2019 the accumulated data were collected from the OJK. Findings - The results showed that in the long term all variables were significant, while in the short term all variables did not have a significant effect. The measure of significance was the T-table value of 1,697. Originality/Value - This study raises the NPF, CAR, FDR, BOPO and NOM with the latest data,  until June 2019